1, 2‐Bis(ferrocenyl)‐Substituted Distibene and Dibismuthene: SbSb and BiBi Units as π Spacers between Two Ferrocenyl Units. Issue 4 (1st February 2013) - Sakagami, Michiyasu; Sasamori, Takahiro; Sakai, Heisuke; Furukawa, Yukio; Tokitoh, Norihiro
<x xml:space="preserve">Abstract</x> Pi in the sky: 1, 2‐bis(ferrocenyl)distibene and 1, 2‐bis(ferrocenyl)dibismuthene derivatives, where two bulky ferrocenyl units are bridged by a SbSb and BiBi π spacer, have been synthesized as a new family of novel d–π conjugated systems. Their molecular structures, spectroscopic behavior, and electrochemical properties reveal the SbSb and BiBi units to be effective π‐electron spacers.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>